Colonialism and Independence in Cypriot Prose writings - Herodotou, Maria (Études helléniques / Hellenic Studies, 2011)
This article analyses Cypriot prose writings within the framework of postcolonial theory with a view to showing the evolution of the colonial experience and Cypriot independence as perceived by its writers. It begins with a general introduction to colonialism and its rejection through the development of postcolonial theory. Thereafter it focuses on prose writings from the 1950s –mainly those recording the anticolonial struggle– through which colonialism is subverted. Reference is then made to Lawrence Durrell’s work Bitter Lemons as an example of colonial discourse through which both the anticolonial struggle and the national identity of the Greek-Cypriots are questioned. The ensuing intertextual response, a form of counter discourse from the Greek side, is then examined. The last part briefly deals with the postcolonial scene: in other words how the authors represent independence and the contemporary political developments (mainly conflict between Greeks and Turks) according to different ideologies and positions shaped by the intertwining of past and present.